Synthesis and Characterization of Ni2+-doped TiO2 Nanowires - Loan, Trinh Thi; Huong, Vu Hoang; Dung, Tran Thi; Long, Nguyen Ngoc (VNU Journal of Science: Mathematics - Physics; Vol 32 No 3DO - 10.25073/2588-1124/vnumap.4050, 2016)
Abstract: TiO 2 nanowires doped with different amounts of Ni 2+ ions (from 0 to 18 mol%) were synthesized by hydrothermal technique. The samples were characterized by X-ray diffraction (XRD) and Raman spectroscopy, field emission scanning electron microscopy (FESEM), and diffuse reflection spectroscopy. The XRD analysis showed that the doped samples exhibit anatase single phase. The lattice parameters remain unchanged, independent on Ni 2+ content. Diameter of TiO 2 nanowires increased significantly with increasing concentrations of Ni 2+ . The investigated results indicate that a greater portion of the Ni 2+ ions are well-incorporated into the anatase TiO 2 lattice. Indirect and direct band gap energies of Ni 2+ -doped TiO 2 with different doping concentration were found to be in the range from 3.24 to 2.99 eV and 3.54 to 3.35 eV, respectively.   Keywords: TiO 2 :Ni 2+ nanowires, hydrothermal, diffuse reflection, band gap energy.